Diversity And Foraging Behaviour Of Insectivorous Birds In Limestone Areas In Lenggong Valley, Perak - Mansor, Mohammad Saiful (2012)
Bird surveys were conducted in the Bukit Kepala Gajah limestone area in Lenggong Valley, Perak from July 2010 to July 2011. The main objectives of this study were to describe the foraging patterns of insectivorous birds in lowland rainforest, and to compare the foraging strategies of insectivorous birds in the continuous and small forest patches. In addition, this study were to determine the influences of initial and sequential observation methods on foraging data of birds, and to examine the influences of habitat structure and disturbance on the bird species composition.